Can we minimize the long-term side effects of immunosuppressive drugs in pediatric patients? - Tönshoff, Burkhard; Mehls, Otto; Weber, Lutz T. (Immunosuppression under trial, 1999)
Renal transplantation is the treatment of choice for end-stage renal disease in children, leading to substantial improvement in the quality of life. However, despite a significant improvement in short-term results, important long-term problems remain unsolved. Allograft half-life has only slightly improved in pediatric renal transplant recipients during the last decade due to the lack of effective treatment for chronic rejection, frequent recipient non-compliance, particularly in adolescence, and nephrotoxicity of the immunosuppressive calcineurin inhibitors cyclosporine A and tacrolimus. Therefore, a pediatric renal graft recipient is likely to need several retransplantations during his life. Furthermore, the immunosuppressive drugs used today have potentially serious side effects, including infection, nephrotoxicity and de novo malignancy. These topics are particularly relevant for children who are likely to receive immuno-suppressive therapy for several decades. The biological differences between an adult and a growing and developing pediatric transplant recipient also have to be taken into account. It is important, therefore, to develop immunosup-pressive protocols that are adjusted to the specific needs of a growing child.
Gesehen am 13.01.2021